2005
DOI: 10.1002/chem.200401067
|View full text |Cite
|
Sign up to set email alerts
|

Microheterogeneous Solvation for Aminolysis Reactions in AOT‐Based Water‐in‐Oil Microemulsions

Abstract: A kinetic study was carried out on the aminolysis of p-nitrophenyl acetate (NPA) by n-decylamine (DEC), piperazine (PIP) and sarcosine (SAR) in AOT/isooctane/water (w/o) microemulsions. By using the pseudophase model both the rate constants at the interface, k2i, and the water microdroplet, k2w, can be obtained. The obtained results show that k2i increases together with the water content of the microemulsion, whereas k2w increases as the water content of the system decreases. In the aqueous microdroplet the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Other reactions that can illustrate this case are the aminolysis of NPA in AOT-based microemulsions by piperazine and sarcosine [20]. In this case, the fit of the pseudophase model equation to the experimental results was satisfactory.…”
Section: Reactions Taking Place Simultaneously In Two Phases: Reactiomentioning
confidence: 58%
See 1 more Smart Citation
“…Other reactions that can illustrate this case are the aminolysis of NPA in AOT-based microemulsions by piperazine and sarcosine [20]. In this case, the fit of the pseudophase model equation to the experimental results was satisfactory.…”
Section: Reactions Taking Place Simultaneously In Two Phases: Reactiomentioning
confidence: 58%
“…Other examples of this case are the aminolysis of NPA by n-decylamine [20] and N-methyl-benzylamine [21] (Scheme 5) or the nitrosation of N-methyl-benzylamine by ethoxy-ethyl-nitrite and bromo-ethyl-nitrite (RONO) in water/AOT/isooctane microemulsions [17] (see Scheme 4).…”
Section: Reactions Taking Place In One Phase: Reaction At Aot Filmmentioning
confidence: 98%
“…From Scheme and using the distribution constants of 2‐nitroaniline defined in terms of molar ratios as shown in Equations (1 a and b) [10] :, the following expression is obtained for absorbance as a function of the composition parameter Z of the microemulsion, Z= [isooctane]/[NaOT]. Note that the concentrations in Equations (1a and b) are in relation to the total volume of the system 11. Considering that the absorbance A at any wavelength is due to that exhibited by 2‐nitroaniline in each microenvironment of the colloidal system, Equation (2) is obtained (for a full derivation see http://www.wiley-vch.de/contents/jc_/<~CRYR>/_s.pdf): where ${\varepsilon _0 }$ and ε i are the molar absorptivities of 2‐nitroaniline in the continuous medium and the interface of the w/o microemulsion, and ${K_{\rm{o}}^{\rm{w}} = K_{{\rm{oi}}} /K_{{\rm{wi}}} }$ .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown its application to aminolysis reactions occurring both in the aqueous microdroplet and at the interface of AOTbased microemulsions. 16 Equivalent expressions to those derived by us were obtained by Casavino and co-workers and applied to iron(III) oxidation of some alkyl-substituted ferrocenes 17 and the kinetics of substitution in palladium(II) complexes. 18 Sánchez et al have shown that the Brönsted equation, which can be derived directly from the transition state theory, is an alternative to the pseudophase model to rationalize the observed kinetic effects in microemulsions.…”
Section: Introductionmentioning
confidence: 88%
“…29 Thus, we can estimate that the decrease in the rate constant is 23 times on going from the aqueous medium to the interface of the microemulsion, an inhibition that is entirely consistent with the behavior observed for other aminolysis reactions in AOT-based microemulsions. 16 2. Reaction in the Continuous Medium.…”
Section: Methodsmentioning
confidence: 99%